Statistical Study of Heavy Ion Outflows From Mars Observed in the Martian‐Induced Magnetotail by MAVEN. Issue 7 (22nd July 2019) - Inui, S.; Seki, K.; Sakai, S.; Brain, D.A.; Hara, T.; McFadden, J.P.; Halekas, J.S.; Mitchell, D.L.; DiBraccio, G.A.; Jakosky, B.M.
Abstract: It is important to include the effects of cold ions when we consider heavy ion outflows from Mars. We here report on statistical properties of heavy ion outflows (including cold ion outflows) observed by Mars Atmosphere and Volatile EvolutioN in the optical wake region. Using data from July 2015 to December 2017, we statistically investigate the effects of solar wind convection electric fields and crustal magnetic fields on the heavy ion outflows. Results show that the average density ratio of O + :O2 + :CO2 + is ~29:68:04. In the southern hemisphere where the strong crustal magnetic fields are located, the heavy ion outflow flux becomes smaller and the relative contribution of molecular ions to heavy ion outflows is larger than the northern hemisphere. The solar wind convection electric field strongly affects the heavy ion outflows. Heavy ion density is larger in the −E (electric field) hemisphere than in the +E hemisphere, while the dependence of velocity is opposite. Acceleration by the solar wind convection electric field in the +E hemisphere is expected to cause these dependencies. The heavy ion flux is larger in the −E (total O: 8.6 × 10 6 cm –2 /s) than in the +E hemisphere (2.9 × 10 6 cm –2 /s) due to the large density in the −E hemisphere. Velocity ratios of O + to O2 + suggest that heavy ion outflows with large velocities tend to have the same energy to each other, while the O + to O2 + ions are more likely to have the same velocity in outflows with small velocities. Plain Language Summary: While Martian climate is cold and dry at present, it is thought that Martian climate was relatively warm and wet about 4 billion years ago. In order to cause this climate change, a vast majority of CO2 existing in the ancient Mars must have been removed from Martian atmosphere. Ion escape from the Martian upper atmosphere to space is one of the candidate mechanisms to remove CO2 . However, the detailed characteristics of ion escape are far from understood. Based on observations in the Martian‐induced magnetotail by the Mars Atmosphere and Volatile EvolutioN mission, we here report on the statistical trend of heavy ion outflows. The effects of electric fields induced by the motion of solar winds and crustal magnetic fields on heavy ion outflows are investigated. Key Points: Heavy ion outflows in the wake region are denser and slower in −E (electric field) hemisphere than in +E hemisphere Heavy ion flux is smaller in the southern hemisphere than the northern, while the relative contribution of molecular ions is larger Fast outflows tend to have the same energy for O + and O2 + ions, while they have more chance to have the same velocity in slow outflows